On the issue of teaching the ukrainian language to foreign citizens: problems and prospects - Abramova, I. G.; Абрамова, Інна Георгіївна (Одеса : Видавничий дім “Гельветика”, 2022)
The need for foreign students to learn Ukrainian is extremely important, as it is associated with high demand and the desire of foreigners to study in Ukraine.